Pregnancy and Delivery in Ehlers-Danlos Syndrome (Hypermobility Type): Review of the Literature - Indranil Dutta; Helen Wilson; Odiri Oteri (Obstetrics and Gynecology International)
Ehlers-Danlos syndrome (EDS) is a group of connective tissue disorders which are divided into various distinguishable phenotypes. The type of EDS determines the potential obstetric complications. Due to the spectrum of clinical manifestation and overlap between phenotypes, there are no standardised obstetric management guidelines. Existing literature illustrates different obstetric management in hypermobility type of EDS, including uneventful term vaginal deliveries as well as preterm cesarean section deliveries. This paper discusses obstetric management of a woman with EDS hypermobility type. Cesarean section was deemed the most appropriate delivery method in this patient due to the possible complications including risk of joint dislocation and pain morbidity. No obstetric complications were experienced, and good maternal and neonatal outcomes were achieved.